103k views
4 votes
Fill in the blank.-8(2x+6)+6(-3+___x)=26x-66

User Chus
by
5.4k points

1 Answer

6 votes

Let call the number in the blank A, then:

-8(2x+6)+6(-3+Ax)=26x-66

If we solve the left side, using distributive property we get:

-16x - 48 - 18 + 6Ax = 26x - 66

-16x + 6Ax - 66 = 26x - 66

Adding 66 on both sides:

-16x + 6Ax - 66 + 66 = 26x - 66 + 66

-16x + 6Ax = 26x

It means that:

-16 + 6A = 26

Solving for A:

-16 + 6A ´+ 16 = 26 + 16

6A = 42

6A/6 = 42/6

A = 7

So, the answer is 7

User Kuzdogan
by
5.3k points